-8/9+3t=73/9

Simple and best practice solution for -8/9+3t=73/9 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -8/9+3t=73/9 equation:


t in (-oo:+oo)

3*t-8/9 = 73/9 // - 73/9

3*t-8/9-(73/9) = 0

3*t-8/9-73/9 = 0

3*t-9 = 0 // + 9

3*t = 9 // : 3

t = 9/3

t = 3

t = 3

See similar equations:

| 4/5x-7=-27/5 | | 1/3d-5/8=-37/40 | | -1/2-6w=29/14 | | -1/9-x=-82/9 | | 4d+9=23/3 | | -2x^2-9x+1=-x^2-2x-4 | | d+8=50/7 | | 7/9+m=-74/9 | | 3b+4=41/8 | | 5-d=5 | | 1-5k=-19 | | 2/7+6a=199/35 | | 4a-1/3=-43/21 | | -2/5(10x-15y) | | 1+k=7/6 | | -7d+2/3=-17/6 | | -5/6x+4/7=248/189 | | 4/5x-8/5=-16/5 | | 2-3/7x=17/7 | | 8+1/3b=22/3 | | 7/8+5d=-33/8 | | -13=-2x+1 | | 4x^2+x+2=-7x+7 | | ln(x-4)-ln(x+3)=2 | | 3.6M-6=26.2-M | | 5t-1=44 | | 5k-2/9=41/18 | | 4n+3=-37 | | 2t+1/3=-1/6 | | -1/3w+2=12/7 | | 4/5k+3/4=-113/20 | | 2/3t+2/7=206/231 |

Equations solver categories